The Influence of Printed Teaching Material on Students’ Cognitive Learning Outcomes - Ami, Mucharommah Sartika; Aminah, Mucharommah Dewi (LPPM Universitas KH. A. Wahab Hasbullah, 2025)
Printed teaching materials are still relevant to be used as learning resources for students. Through this research we analyze the effect of printed modules on students’ cognitive learning outcomes in plant physiology courses. We used the one-shot case study method involving 12 students taking plant physiology courses in the 2024/2025 academic year. The cognitive learning outcomes used as data are mid-semester and final semester exam scores. Data analysis was carried out by sign test. The significance level used is 5%, H0 is rejected if the calculated value is smaller than the table value. H0 in this research is that there is no effect of using printed modules on student cognitive learning outcomes. The sign test results show that the calculated h value is greater than the table h value, so H0 is accepted. The use of printed modules did not affect students’ cognitive learning outcomes in this study.